2021
DOI: 10.1007/s12220-021-00718-w
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Conditions for Ultradifferentiability

Abstract: A remarkable theorem of Joris states that a function f is $$C^\infty $$ C ∞ if two relatively prime powers of f are $$C^\infty $$ C ∞ . Recently, Thilliez showed that an analogous theorem holds in Denjoy–Carleman classes of Roumieu type. We prove that a division property, equivalent to Joris’s result, is valid in a wide variety of ultradifferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In the recent paper [15] Thilliez showed that this result carries over to Denjoy-Carleman classes of Roumieu type and, by refining Thilliez's method, we proved in [11] that it is valid in a wide variety of ultradifferentiable classes. See the introduction in [11] for more on the historical development.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…In the recent paper [15] Thilliez showed that this result carries over to Denjoy-Carleman classes of Roumieu type and, by refining Thilliez's method, we proved in [11] that it is valid in a wide variety of ultradifferentiable classes. See the introduction in [11] for more on the historical development.…”
Section: Introductionmentioning
confidence: 76%
“…A function f is smooth provided that two relatively prime powers or, equivalently, two consecutive powers of f are smooth, by a theorem of Joris [4]. In the recent paper [15] Thilliez showed that this result carries over to Denjoy-Carleman classes of Roumieu type and, by refining Thilliez's method, we proved in [11] that it is valid in a wide variety of ultradifferentiable classes. See the introduction in [11] for more on the historical development.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations